PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI BALAI SIDANG JAKARTA CONVENTION CENTER - Veronika Puji Lestari; Bambang NS (LPPM Universitas Asa Indonesia, 2016)
Purpose- This study aims to determine the training and compensation partially and simultaneously influence on employee performance Design/methology/approach- The population in this study are employees at Balai Sidang Jakarta Convention Center which has 130 employee. The sample used in this study were 100 employees of the Balai Sidang Jakarta Convention Center, the sampling technique used was accidental sampling. Data analysis tool used in this research is multiple linear regression, validity, reliability, classical assumption (normality test, multicollinearity test, heteroscedasticity test and linearity test). While testing the hypothesis includes the F-test, t test, and analysis of partial correlation and coefficient of determination (R2). Findings- From the analysis it can be seen that training and compensation have an influence on employee performance partially or simultaneously. Research limitations- The limitation of this research lies on its scope of object, and the limited variables involved. It I s then suggested for the next research that other variable such as compensation, and other exogen variable can be deployed too. This results may not be applicable in the same line of business. Practical implications- The manager of human resource shall maintain and develop the potential of employees by providing a combination of training and motivation in human resourcesopment. The Originality- This is done exclusively for the Jaskarta Convention Centre.